Lesion-Specific Peri-Coronary Fat Attenuation Index Is Associated With Functional Myocardial Ischemia Defined by Abnormal Fractional Flow Reserve - Ma, Shaowei; Chen, Xujiao; Ma, Yue; Liu, Hui; Zhang, Jiayin; Xu, Lei; Wang, Yining; Liu, Ting; Wang, Kunhua; Yang, Jinzhu; Hou, Yang (Frontiers in Cardiovascular Medicine, 2021)
Background: The association between abnormal invasive fractional flow reserve (FFR) and the fat attenuation index (FAI) of lesion-specific peri-coronary adipose tissue (PCAT) is unclear. Method: Data of patients who underwent coronary computed tomography angiography (CTA) and subsequent invasive coronary angiography (ICA) and FFR measurement within 1 week were retrospectively included. Lesion-specific FAI (FAIlesion), lesion-free FAI (FAInormal), epicardial adipose tissue (EAT) volume and attenuation was collected, along with stenosis severity and plaque characteristics. Lesions with FFR <0.8 were considered functionally significant. The association between FFR and each parameter was analyzed by logistic regression or receiver operating characteristic curve. Result: A total of 227 patients from seven centers were included. EAT volume or attenuation, traditional risk factors, and FAInormal (with vs. without ischemia: −82 ± 11 HU vs. −81 ± 11 HU, p = 0.65) were not significantly different in patients with or without abnormal FFR. In contrast, lesions causing functional ischemia presented more severe stenosis, greater plaque volume, and higher FAIlesion (with vs. without ischemia: −71 ± 8 HU vs. −76 ± 9 HU, p < 0.01). Additionally, the CTA-assessed stenosis severity (OR 1.06, 95%CI 1.04–1.08, p < 0.01) and FAIlesion (OR 1.08, 95%CI 1.04–1.12, p < 0.01) were determined to be independent factors that could predict ischemia. The combination model of these two CTA parameters exhibited a diagnostic value similar to the invasive coronary angiography (ICA)-assessed stenosis severity (AUC: 0.820 vs. 0.839, p = 0.39). Conclusion: It was FAIlesion, not general EAT parameters, that was independently associated with abnormal FFR and the diagnostic performance of CTA-assessed stenosis severity for functional ischemia was significantly improved in combination with FAIlesion.